Improved reproductive outcomes in normogonadotropic oligomenorrheic women undergoing ovarian stimulation with intrauterine insemination: a retrospective cohort analysis of real-world data - Li, Sichen; Long, Yao; Wang, Chunyan; Yang, Rui; Lv, Junye; Chen, Zixin; Liu, Jianqiao; Liu, Haiying; Cao, Mingzhu (Frontiers in Endocrinology, 2024)
Purpose: This study aimed to evaluate the comparative reproductive outcomes of ovarian stimulation combined with intrauterine insemination using partner's sperm (OS-IUI) in eumenorrheic and normogonadotropic oligomenorrheic women.: A retrospective cohort study was conducted, including 3833 couples who underwent 5920 cycles of OS-IUI between June 2013 and March 2019. Participants were stratified into two cohorts based on menstrual regularity: eumenorrheic and normogonadotropic oligomenorrheic. The primary outcome measured was the live birth rate (LBR) per cycle and cumulative LBR per couple. Secondary outcomes encompassed the clinical pregnancy rate (CPR) per cycle, miscarriage rate, and multiple pregnancy rate. Propensity score matching (PSM) was utilized to balance maternal baseline characteristics.Results: Prior to PSM, significant differences in CPR, LBR and cumulative LBR were observed between eumenorrheic and oligomenorrheic women, favoring the latter (CPR: 11.16% vs. 18.75%; LBR: 9.02% vs. 14.96%; cumulative LBR: 13.60% vs. 24.25%, P < 0.001). These differences persisted post-PSM (CPR: 9.74% vs. 19.29%; LBR: 7.30% vs. 16.29%; cumulative LBR 7.76% vs. 19.90%, P<0.001). Multivariate regression analyses revealed that menstrual status was a significant independent predictor of both CPR (adjusted odds ratio [OR]=1.83 before PSM, 2.24 after PSM) and LBR (adjusted OR=1.90 before PSM, 2.46 after PSM). In the subgroup analysis, female age was identified as the sole predictor of reproductive outcomes in oligomenorrheic women undergoing OS-IUI. Conversely, in eumenorrheic women, factors such as age, duration of infertility, body mass index (BMI), ovarian stimulation agents, and the number of dominant follicles were significant influencers of CPR and LBR.Normogonadotropic oligomenorrheic women demonstrated improved reproductive outcomes with OS-IUI, suggesting that tailored treatment strategies based on menstrual regularity could optimize success rates in infertility management.